Wild World : An Encyclopedia of Animals - Johnson, Jinny (London Weldon Owen, 2012)
Pictures and text show how different animals use posture, plumage, or other natural decoration to warn, elude, or engage in courtship.
Includes Index, Glossary and Colred Illustrations.
Animal Planet (Television Network)
Keywords: Animals -- Habits and behavior